Assimilation, Criminality and Ethnic Conflict - Indraneel Dasgupta; Diganta Mukherjee (Institute for the Study of Labor (IZA), 2014)
We examine the consequences, of integrating large minorities into productivity-relevant majority ethno-linguistic norms, for distribution, ethnic conflict and crime. We develop a two-community model where such assimilation generates social gains by: (a) facilitating economic interaction, and (b) dampening religious or racial conflict over symbolic and normative contents of the public sphere. However, integration shifts the distribution of both material and symbolic goods against the minority. It also expands income inequality within the minority community. This incentivizes decentralized attempts to expropriate producers which, through cumulative causation, both immiserize and criminalize the minority. An underclass thus results, with disproportionate minority presence.
Keywords: D74; J15; J71; O15; Z13; 330; minority; identity; language; assimilation; discrimination; ethnic conflict; crime; welfare dependency